Ecological paradigm of integrated plant management - Mostovjiak І. (Quarantine and plant protection, 2019)
Goal. Analysis and synthesis of the current state of development of integrated plant protection (Integrated Pest Management, IPM) in Europe and Ukraine. Methods System-analytical, abstract-logical, empirical. Results. The basis of agricultural production is the creation of artificial agro-ecosystems with the aim of obtaining the largest possible amount of products and profits per unit area. The productivity of agrobiocenosis is determined by the level of additional technological energy, a significant proportion of which are measures of protection against pests, plant diseases, and weeds. IPM is a reliable pest control paradigm all over the world and has been included in state policy and regulations in the European Union. In line with the EU Framework Directive 2009/128/EC, there are eight IPM principles that all EU members have to comply with strictly from January 2014. They include the prevention and suppression by nonchemical methods, pest monitoring, management. Biological, physical and other non-chemical methods should be used in the first place, and selective pesticides, which have a small negative impact on human health and on useful insects — only if necessary. In order to prevent the development of resistance in pest populations, the use of pesticides should be kept to a minimum by reducing the doses and frequency of their use and the pesticides should be used with different mechanisms of action. It is also important to evaluate the integrated plant protection program. Conclusions. In this paper, information on the history, concepts, principles, components, and methods of integrated plant protection in the world, as well as the application of these methods in Ukraine, was generalized. At present, the implementation of IPM principles in Ukraine is insufficient and requires a systematic approach and a joint action of many parties: scientists, farmers, specialists in the production and marketing of agricultural products, and politicians.